IDENTIFICATION OF THE ELEMENTS OFTHE MECHANISM FOR ENSURING RESILIENCE OF THE SOCIO-ECONOMIC SYSTEM OF THE ENTERPRISE (Development Service Industry Management, 2024)
In the study, attention is updated to the problem of ensuring the resilience of Ukrainian business in the conditions of war and the critically acute socio-economic instability caused by it. The purpose of the article is to identify and substantiate the elements of the mechanism for ensuring the resilience of the socio-economic system of Ukrainian enterprises in crisis conditions. It is argued that critical instability and the most difficult conditions for ensuring the viability of Ukrainian enterprises in the conditions of a full-scale war naturally determine the high urgency of developing new methodological and applied approaches to ensuring their resilience, and the basis of such practices, undoubtedly, is the formation and implementation of the appropriate socio-economic mechanism. The configuration and composition of the structural elements of the mechanism for ensuring the resilience of the socio-economic system of the enterprise is determined. The peculiarities and place of the mechanism for ensuring the resilience of the socio-economic system of domestic enterprises have been studied. The formation and implementation in practice of the mechanism for ensuring the resilience of the socio-economic system of domestic enterprises should be a clearly institutionalized process that takes place on an ongoing basis in accordance with the planned phasing of measures and their results on the way to achieving the defined general goal. The most rational and effective basis of such an approach is the use of an organizational and economic mechanism, the organizational unit of which is responsible for building a safety management system, and the economic unit is responsible for the formation of a motivational field for achieving the goal and realizing the socio-economic interests of stakeholders in the system of operation and development of enterprises. The elements of the management mechanism are its purpose, goals, principles, methods, functions, tools, conceptual basis, the environment for the formation of resource provision and control.
Keywords: enterprise management; socio-economic system; resilience; sustainability and stability; economic security; security mechanism